2014
DOI: 10.3109/03009734.2014.899279
|View full text |Cite
|
Sign up to set email alerts
|

Combination antibiotic therapy for multidrug-resistant Gram-negative bacteria

Abstract: Combination antibiotic therapy for Gram-negative sepsis is controversial. The present review provides a brief summary of the existing knowledge on combination therapy for severe infections with multidrug-resistant Pseudomonas spp., Acinetobacter spp., and Enterobacteriaceae. Empirical combination antibiotic therapy is recommended for severe sepsis and septic shock to reduce mortality related to inappropriate antibiotic treatment. Because definitive combination therapy has not been proven superior to monotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 48 publications
(27 reference statements)
0
109
0
3
Order By: Relevance
“…In the recent study, a combination of meropenem with minocycline was synergistic to tested XDR (extensively drug-resistant) A. baumannii isolates, but neither showed bactericidal activity alone. Furthermore, the authors observed that also colistin and meropenem presented synergistic effect and showed bactericidal activity against all tested strains [54,55].…”
Section: Clinical Usementioning
confidence: 97%
“…In the recent study, a combination of meropenem with minocycline was synergistic to tested XDR (extensively drug-resistant) A. baumannii isolates, but neither showed bactericidal activity alone. Furthermore, the authors observed that also colistin and meropenem presented synergistic effect and showed bactericidal activity against all tested strains [54,55].…”
Section: Clinical Usementioning
confidence: 97%
“…Antibiotic combinations of colistin plus rifampin (23), ertapenem plus doripenem (27), tigecycline plus colistin, fosfomycin plus meropenem, and colistin plus carbapenem (imipenem, meropenem) were extensively studied against colistin resistant Klebsiella pneumoniae. Combinations of colistin-carbapenem or an aminoglycoside, tigecycline, fosfomycin, and rifampin have been advocated for carbapenemase-producing Klebsiella species (28)(29)(30)(31)(32). In addition, 3 drug combinations were also assessed to have benefited imipenem plus tigecycline in combination with amikacin showed bactericidal activity (23,33).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the synergistic effect of colistin-meropenem by checkerboard method was 86% (21/24) and by the timekill studies were 76% (16/21). In modified time-kill analysis, our aim was to expose the isolates initially with colistin and the later addition of meropenem at different time intervals, which allows colistin to disrupt the outer cell membrane making easy permeability of carbapenem (30,31). Depending on the mechanisms of action, both colistin and meropenem in combination can act as a bactericidal (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…However, emergence of resistance to these antimicrobial agents has also been reported (8). Notwithstanding, combination therapy has been considered superior to single-drug therapy against MDRAB, with regards to both efficacy and lower risk of adverse reactions and drug toxicity (9)(10)(11). Tigecycline based therapy with various combinations such as cefoperazone-sulbactam, carbapenem, quinolone, or aminoglycoside antibiotics, has been adopted for treatment of MDRAB infections (12,13).…”
Section: Introductionmentioning
confidence: 99%